BIOMONITORING PENCEMARAN TANAH MENGGUNAKAN CACING TANAH (Lumbricus rubellus) - Eka Sulistiyawati; Ratna Ariyanti; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Earthworms (Lumbricus rubellus) can be used as bioindicators of soil pollution due to their high sensitivity to changes in environmental conditions and their ability to accumulate pollutants in their bodies. Changes in earthworm behavior, growth, reproduction, and survival rates can reflect the level of pollution in the soil. Using earthworms as bioindicators is an effective, simple, and environmentally friendly method for biomonitoring soil quality and can assist in sustainable environmental management and conservation efforts. Keywords: Bioindicators, Earthworms, Pollution